Answer:
Therefore , [tex]y= \frac{Ae^{kt}}{1+Ae^{kt} }[/tex]
Step-by-step explanation:
The fraction of population who have heard rumor = y
The fraction of population who haven't heard rumor = 1-y
The rate of of spread (y'(t)) is proportional to the product of the fraction of population who have heard rumor the fraction of population who have heard rumor.
Therefore
y'(t) ∝ y (1-y)
⇒ y'(t) =k y (1-y) [ k = constant of proportional]
[tex]\Rightarrow \frac{dy}{dt}=ky(1-y)[/tex]
[tex]\Rightarrow \frac{dy}{y(1-y)}=k \ dt[/tex]
Integrating both sides
[tex]\Rightarrow \int\frac{dy}{y(1-y)}=\int k \ dt[/tex]
[tex]\Rightarrow \int \frac{dy}{y}+\int\frac{dy}{1-y}=\int k \ dt[/tex] [tex][\because \frac{1}{y(1-y}=\frac{1}{y}+\frac{1}{1-y} ][/tex]
[tex]\Rightarrow ln \ y- ln \ |1-y| = kt +c[/tex] [ c = arbitrary constant]
[tex]\Rightarrow ln|\frac{y}{1-y}|=kt +c[/tex]
[tex]\Rightarrow \frac{y}{1-y}= e^{kt+c}[/tex]
[tex]\Rightarrow \frac{y}{1-y}= Ae^{kt}[/tex] [ Here [tex]e^c=A[/tex] ]
[tex]\Rightarrow y = Ae^{kt}(1-y)[/tex]
[tex]\Rightarrow y = Ae^{kt}-y Ae^{kt}[/tex]
[tex]\Rightarrow y+y Ae^{kt} = Ae^{kt}[/tex]
[tex]\Rightarrow y(1+Ae^{kt} )= Ae^{kt}[/tex]
[tex]\Rightarrow y= \frac{Ae^{kt}}{1+Ae^{kt} }[/tex]
Therefore , [tex]y= \frac{Ae^{kt}}{1+Ae^{kt} }[/tex]